What Matters: Achieving Racial Equity in a Human Service Non-Profit Organization - Curry-Stevens, Ann (Advances in Social Sciences Research Journal, 2022)
Few research studies exist on the efforts and outcomes undertaken by non-profits aiming to integrate racial equity into their organization. This article, through case study research, identifies how Metropolitan Family Service (in Portland, Oregon) has make seven key gains over the last decade: staff diversification, cultural shift in the organization, board development, data systems that support disaggregation, meaningful community partnerships, high client satisfaction, and most important, more equitable service outcomes. In additional to sharing details on these gains, this article identifies the features of how this organization believes that it has actualized these outcomes: through a range of cultural features that support racial equity, and through a counselling model that centers cultural respect and support. Both are shared in this article. The article concludes with a synthesis of advice for the non-profit field.